Microplastics in a pelagic squid (Dosidicus gigas) from the Eastern tropical Pacific Ocean: Characteristics, spatial variation, and preliminary risk assessment - Wang, Yaxin; Chen, Xinjun (Frontiers in Environmental Science, 2023)
Despite concerns about the environmental impact of microplastics (MPs), knowledge of MP contamination levels in pelagic squid is lacking. This study investigated the stomach of an ecologically and commercially important but poorly known squid species, the jumbo squid Dosidicus gigas, found in the tropical and southern temperate Pacific. We examined the characteristics and spatial distribution of MPs in fifty D. gigas (16.0 to 37.8 cm mantle length) and assessed potential MP pollution risks. MPs were detected in 50.0% of specimens and had an average abundance of 0.88 ± 1.12 items/individual and 0.24 ± 0.36 items/g stomach weight, and were sized 58.42 to 2944.85 μm. The MPs were dominated by polyethylene terephthalate (31.82%) in polymer type, fragments (54.55%) and fibers (43.18%) in shape, and blue (59.59%) in color. All specimens could be evaluated as low risk. No statistically significant correlations were found between the MP abundances and D. gigas stomach weight, stomach fullness index, distance from the coast, and mantle length. While regression analyses showed that fuller stomachs contained larger MPs. Spatial variations in shape and polymer composition suggest that low-density fibrous MPs could be easily transported offshore by upwelling and/or ocean currents. These results indicate intraspecific variation in D. gigas MP contaminants and underscore the need to assess the potential site-specific ecotoxicological consequences of increased plastic pollution to pelagic squid.